Brand Storytelling Melalui Pendekatan Morfo-Semantik Pada Tradisi Syawalan Kupat Jembut di Pedurungan Semarang - Ngatoillah Linnaja; Robingun Suyud El Syam; Salis Irvan Fuadi (Pusat riset dan Inovasi Nasional, 2023)
This research is to uncover brand storytelling through a morpho-semantic approach to the tradition of kupat jembut syawalan in Pedurungan Semarang. This article is the finding of a descriptive study using Ogden & Richard's semantic approach, using Crespo's storytelling theory of the Syawalan kupat-jembut tradition in Semarang, then analyzing its morphology to see its essence. The results of the study show: that the kupat jembut is used as a medium to attract the community so that the Syawalan tradition of the Pedurungan Semarang community can be preserved for the next generation. The naming does not reduce the essence of syawalan which is an expression of gratitude and hospitality. The research implication, narrative experience brings understanding to the essence of Islamic tradition to be preserved. Research is expected to contribute to Islamic cultural scholarship. Keyword: , , ,